Counteracting malicious adversaries via secret and reliable coding mechanism in random network coding - Chen, Siguang; Wu, Meng; Lu, Weifeng (International journal of communication systems, 2013)
SUMMARYThis paper investigates the problem of constructing a secret and reliable network coding communication scheme against an adversary that can reselect the μ tapping links in different time slices and inject z erroneous packets into the network, while the network suffers from ρ packet erasures. We first derive a necessary condition for keeping the transmitted information secret from the adversary, while the network is only subject to eavesdropping attack, and no errors are injected. We then provide two network coding schemes for error and erasure correction, which can decode the transmitted information correctly. With that, a secret and reliable network coding is proposed by combining two error and erasure correction schemes with secret communication. We show that under the requirement of 2z + ρ+ μ  <  k ⩽2z + 2ρ communication can achieve a rate of k −μ−z −ρ packets, where k denotes the network capacity. Moreover, it ensures that the communicated information has complete reliability and information‐theoretic security from the adversary. In particular, the requirement of packet length does not need to be sufficiently large, which is close to the practical packet length. Finally, we also compare our scheme's performance with existing work; the numeric results and security analyses illustrate the performance and security of our scheme. Copyright © 2011 John Wiley & Sons, Ltd. In this paper, we construct a secret and reliable network coding scheme against an adversary that can reselect the μ tapping links in different time slices and inject z erroneous packets into the network, while the network suffers from ρ packet erasures. We show that under the requirement of 2z + ρ+ μ  <  k  ⩽ 2z + 2ρ communication can achieve a rate of k −μ−zρ packets, where k denotes network capacity. In particular, the requirement of packet length doesn't need to be sufficiently large, which is close to the practical packet length.